PENGARUH KEPERCAYAAN SOSIAL MEDIA INSTAGRAM PADA PERKEMBANGAN TEKNOLOGI INFORMASI TERHADAP NANO DAN MICRO INFLUENCER PADA APLIKASI THE ASIAN PARENT INDONESIA - Nuning Khanif Aulia (Jurnal Teknik dan Science, 2025)
This research was conducted within The Asian Parent community, which directly engages in projects aimed at introducing or influencing a specific audience regarding events or products for certain brands. The data collection technique used random sampling among influencers, utilizing a Nomogram table with a confidence level of 98% or a margin of error of 2%. This study falls under the category of direct survey research with a quantitative approach. Data collection was carried out through an online questionnaire.